Faba bean enhances soil multifunctionality through shaping rhizosphere microbial communities in legume-cereal crop rotations - Yixuan CHEN; Zhijie DONG; Yu WANG; Qiong LIU; Kailu ZHANG; Ruohan YIN; Jianping Chen; Tida GE; Zhenke ZHU (Frontiers of Agricultural Science and Engineering)
Crop rotation is a beneficial and sustainable agricultural practice that facilitates increased opportunities for smallholders. This study investigated the impact of eight commonly used crop rotations in China on soil properties and microbial communities. The faba bean (Vicia faba) rotation increased soil water content, total carbon, total nitrogen, total phosphorus and organic carbon content by 29.1%, 40.9%, 55.9%, 18.9%, and 61.6%, respectively, compared to other rotations. The faba bean rotation also exhibited increased soil microbial biomass and soil respiration rates. The effect sizes of the faba bean rotation on soil properties were larger than those of other rotations. The richness and diversity of the microbial community were significantly higher in the faba bean rotation than in other rotations. Desulfobacterota and Planctomycetota had a positive correlation with soil multifunctionality. The faba bean rotation was potentially beneficial to soil fertility and water-use efficiency, creating a favorable niche for microbial growth. With increased microbial activity and potential for nutrient mineralization, legume-microbe interactions had been improved through crop rotation. This resulted in enhancing nutrient cycling efficiency in the faba bean rotation, potentially improving soil properties.